1987
DOI: 10.1093/jn/117.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thyroid Status on Body Weight Gain, Food Intake and Serum Lipid Levels in Genetically Obese Zucker Rats

Abstract: Body weight gain, food intake and serum concentrations of total lipids, cholesterol, triglycerides, phospholipids and free fatty acids were measured in genetically obese and lean female Zucker rats after surgical thyroidectomy and treatment with 3,5,3'-triiodothyronine (T3) (3 micrograms/100 g body wt per day) for 4 wk. There were large differences in the major serum lipids between the control obese and lean rats. Obese rats were characterized by high levels of the various categories of lipids, especially of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is unlikely that this differential feeding response to T3 was due to the relatively larger size and adiposity of the old rats. Prior studies reported that T3 does not decrease food intake in young obese rats (5,15) and that T3 effectively increases food intake in both lean and obese young rats (15). Unlike young obese rats, old rats have a compromised ability to regain weight after food withdrawal, and central orexigenic neuropeptides are less effective in inducing appetite (16).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that this differential feeding response to T3 was due to the relatively larger size and adiposity of the old rats. Prior studies reported that T3 does not decrease food intake in young obese rats (5,15) and that T3 effectively increases food intake in both lean and obese young rats (15). Unlike young obese rats, old rats have a compromised ability to regain weight after food withdrawal, and central orexigenic neuropeptides are less effective in inducing appetite (16).…”
Section: Discussionmentioning
confidence: 99%
“…Since tyrosine is the amino acid precursor of thyroid hormones known to play an important role in the regulation of plasma cholesterol (19,20), a following experiment was carried out to determine if tyrosine availability during protein digestion is a relevant factor which may influence plasma cholesterol in rats, through its effect on plasma thyroid hormone levels (21).…”
Section: Tyrosine Supplementation and Plasma Cholesterolmentioning
confidence: 99%